Client satisfaction among participants in a randomized trial comparing oral methadone and injectable diacetylmorphine for long-term opioid-dependency - Brissette Suzanne; Guh Daphne; Oviedo-Joekes Eugenia; Marchand Kirsten I; Marsh David C; Schechter Martin T (BMC, 2011)
Abstract Background Substitution with opioid-agonists (e.g., methadone) has shown to be an effective treatment for chronic long-term opioid dependency. Patient satisfaction with treatment has been associated with improved addiction treatment outcomes. However, there is a paucity of studies evaluating patients' satisfaction with Opioid Substitution Treatment (OST). In the present study, participants' satisfaction with OST was evaluated at 3 and 12 months. We sought to test the relationship between satisfaction and patients' characteristics, the treatment modality received and treatment outcomes. Methods Data from a randomized controlled trial, the North American Opiate Medication Initiative (NAOMI), conducted in Vancouver and Montreal (Canada) between 2005-2008, was analyzed. The NAOMI study compared the effectiveness of oral methadone vs. injectable diacetylmorphine over 12 months. A small sub-group of patients received injectable hydromorphone on a double blind basis with diacetylmorphine. The Client Satisfaction Questionnaire (CSQ-8) was used to measure satisfaction with treatment. CSQ-8 scores, as well as retention and response to treatment, did not differ between those receiving hydromorphone and diacetylmorphine at 3 or 12 months assessments; therefore, these two groups were analyzed together as the 'injectable' treatment group. Results A total of 232 (92%) and 237 (94%) participants completed the CSQ-8 at 3 and 12 months, respectively. Participants in both groups were highly satisfied with treatment. Independent of treatment group, participants satisfied with treatment at 3 months were more likely to be retained at 12 months. Multivariate analysis indicated that satisfaction was greater among those randomized to the injection group after controlling for treatment effectiveness. Participants who were retained, responded to treatment, and had fewer psychological symptoms were more satisfied with treatment. Finally, open-ended comments were made by 149 (60.3%) participants; concerns about the randomization process and the study ending were most commonly reported by participants receiving the oral and injectable medications, respectively. Conclusions The higher satisfaction among those receiving medically prescribed injectable diacetylmorphine (or hydromorphone) supports current evidence regarding the attractiveness of this treatment for long-term, opioid-dependent individuals not benefiting sufficiently from other treatments. In addition, the measurement of treatment satisfaction provides valuable information about participants at risk of relapse and in need of additional services. Trial Registration ClinicalTrials.gov Identifier: NCT00175357